207k views
1 vote
If f(x) = −-4x^{2} + 15, then f(−3) =

User Zura
by
6.2k points

2 Answers

3 votes

Answer:


\Huge \boxed{-21}

Explanation:


f(x) = -4x^(2) + 15

f(-3), the input is -3 for the function f(x).

The value of x = -3


f(-3) = -4(-3)^(2) + 15

Evaluate the expression.


f(-3) = -4(9)+ 15


f(-3) = -36+ 15


f(-3)=-21

The value of f(-3) is -21.

User Annica
by
5.8k points
0 votes

Answer:

f(-3) = -21

Explanation:

To find f(-3), we just need to plug x = -3 into f(x) so:

f(-3) = -4 * (-3)² + 15

= -4 * 9 + 15 = -36 + 15 = -21

User Laughedelic
by
5.9k points